Developing Flipbook for Teaching Narrative Text through Reading Aloud Strategy - Sari, Dila Permata; Hidayah, Bariqotul; Alimin, Alimin (Universitas Pahlawan Tuanku Tambusai, 2026)
This research was motivated by low student motivation and their difficulties in understanding narrative texts when using conventional teaching materials. Therefore, this research aimed to develop interactive flipbook as a learning media for eighth-grade students at MTs Hasyimiyah. This research followed the Research and Development (RD) method using ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The participants were 77 eighth-grade students who took part in the field trial. Data were collected using validation sheets for experts, observation checklists, and student response questionnaires as the primary instruments. The findings showed that the integration of digital features, such as QR codes for audio models, into the flip-book was feasible and practical for classroom use. These features successfully supported student performance in reading aloud activities, particularly in improving confidence and pronunciation accuracy. The implication of this research is that the flipbook provides a flexible and engaging alternative for English teachers to enhance the quality of reading instruction through technology-integrated media.